1995
DOI: 10.1007/bf00318043
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of bone mineral density of the femurs in hemiplegia

Abstract: We evaluated the bone mineral density (BMD) of the bilateral femurs in 112 patients with hemiplegia using dual-energy X-ray absorptiometry in order to elucidate the effect of disuse and immobilization. BMD of the paretic side was significantly reduced compared with that of the non-paretic side in hemiplegic patients (femoral neck 0.582 +/- 0.014 g/cm2 versus 0.623 +/- 0.014 g/cm2 and total femur 0.645 +/- 0.02 g/cm2 versus 0.702 +/- 0.017 g/cm2; mean +/- SEM, P < 0.01, respectively). Femoral BMD in both the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 13 publications
1
34
1
1
Order By: Relevance
“…First, BMD in the paretic limbs is consistently lower than in the nonparetic limbs (by ≤20%) [38,40,[50][51][52][53][54]. The magnitude of the side-to-side difference found in individuals with stroke is much higher than that found between the dominant and nondominant sides in nondisabled older individuals (<1.5%) [55], which suggests a pronounced effect of hemiparesis on bone loss.…”
Section: Stroke: a Model Of Disuse Osteoporosismentioning
confidence: 95%
“…First, BMD in the paretic limbs is consistently lower than in the nonparetic limbs (by ≤20%) [38,40,[50][51][52][53][54]. The magnitude of the side-to-side difference found in individuals with stroke is much higher than that found between the dominant and nondominant sides in nondisabled older individuals (<1.5%) [55], which suggests a pronounced effect of hemiparesis on bone loss.…”
Section: Stroke: a Model Of Disuse Osteoporosismentioning
confidence: 95%
“…Previous studies in stroke patients have reported 1.3-8.8% side-to-side difference in BMD at various sites in the legs [15,16,20,22,23,[50][51][52]. However, comparison with other studies is extremely difficult for several reasons.…”
Section: Side-to-side Differences In Bone Mineral Levels and Soft Tismentioning
confidence: 96%
“…However, comparison with other studies is extremely difficult for several reasons. First, these studies reported data from patients in different stages of stroke recovery such as acute [22], subacute [15,23,50,51], and chronic [15,50]. Second, many studies included subjects who were non-ambulatory [16,20,22,51,52].…”
Section: Side-to-side Differences In Bone Mineral Levels and Soft Tismentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that bone mineral density is altered in people who are wheelchair-bounded or paralyzed. 39,40 Therefore, DXA could minimize the measurement errors associated with the variations in bone mineral density between the reference body and individuals with physical disabilities. SKF, on the other hand, does not seem to be an appropriate technique for predicting %BF of adults with physical disabilities, including those with SCI.…”
Section: Physical Activity On Body Compositionmentioning
confidence: 99%